Methicillin-resistant Staphylococcus aureus of lineage ST398 as cause of mastitis in cows - Silva, N. C. C. [UNESP]; Guimaraes, F. F. [UNESP]; Manzi, M. P. [UNESP]; Fernandes Junior, A. [UNESP]; Gomez-Sanz, E.; Gomez, P.; Langoni, Hélio [UNESP]; Rall, V. L. M. [UNESP]; Torres, C. (Wiley-Blackwell, 2014)
The objective of this study was to analyse the prevalence and molecular characteristics of methicillin-resistant Staphylococcus aureus (MRSA) in milk of cows with mastitis. The California mastitis test (CMT) was used to detect the presence of mastitis in all 100 cows of a farm in Brazil. The CMT was positive in milk of 115 mammary quarters from 36 cows (36%). MRSA isolates were recovered from 4 of these 36 cows with mastitis (11%), and they were further characterized (one MRSA/sample). The four MRSA isolates were typed as t011-ST398-agr1-SCCmecV and presented two different pulsed-field-gel-electrophoresis-ApaI patterns. These four MRSA isolates showed resistance to tetracycline, streptomycin and ciprofloxacin, carried the mecA, blaZ, tet(K), and tet(M) resistance genes, and presented the S84L and S80F amino acid substitutions in GyrA and GrlA proteins, respectively. Two ST398 isolates exhibited resistance to gentamicin and tobramycin [with aac(6)-aph(2) and ant(4)-Ia genes] and one isolate resistance to clindamycin [with lnu(B) and lsa(E) genes]; this latter isolate also carried the spectinomycin/streptomycin resistance genes spw and aadE. MRSA of lineage ST398 is worldwide spread, normally multidrug resistant and may be responsible for bovine mastitis. To our knowledge, this is the first detection of MRSA-ST398 in Brazil.
Keywords: bovine; mecA; methicillin-resistant Staphylococcus aureus; Staph; aureus; ST398; t011